Corporate governance and firm performance : a comparison between U.S. and SG. - Lim, Eugene Jia Hui. (2011)
The aim of this study is to understand whether corporate governance affects firm performance differently for Singapore firms in comparison to U.S. firms. We compare the governance of selected Singapore (SG) firms to the governance of similar United States of America (U.S.) firms and relate it to various measures of firm performance. We use a governance score index developed by Aggarwal et al. (2007), to measure firm governance attributes and find that on average, SG firms have a lower governance score than matching U.S. firms. For SG firms, we find that Tobin’s Q which is a measure of firm value has significant relation with governance score while for U.S. firms, both Tobin’s Q and Return on Assets (ROA) shows a significant relation. Among the individual governance attributes investigated, we find that a stronger Board improves Tobin’s Q in both SG and the U.S. while other attributes such as Audit only improves ROA in the U.S. When we analyze both Singapore and U.S. sample firms together, we find that ROA is significantly related to corporate governance. We did not find any evidence of corporate governance affecting the SG and U.S. firms differently. Individual governance attributes that are significantly related to ROA in both SG and U.S. firms are Board and Audit attributes.